Professional psychology competency initiatives: implications for training, regulation, and practice. (June 2014) - Rodolfa, Emil; Baker, Jeff; DeMers, Steve; Hilson, Amy; Meck, Donald; Schaffer, Jack; Woody, Sheila; Turner, Matt; Webb, Carol
Psychology in the United States has struggled with defining and specifying competencies for the practice of psychology since the Boulder Conference of 1949 outlined the first training model for graduate programs in psychology. Competency was largely defined by types of experiences and "seat time" until 1986, when the first major competency model in professional psychology in the United States was proposed. By 2000, discussions about the competencies had begun in earnest, and since that time, psychology's focus on competencies has intensified, resulting in a shift away from a model of training that involved tracking the number of hours spent learning specific knowledge or skills to a "culture of competence" that emphasizes outcome, that is, the acquisition of the essential knowledge and skills. In order to develop this culture, competence must first be defined and described. A number of efforts to do so have been completed, initially resulting in a confusing array of different models or perspectives. Over time, however, the models have become more refined and similar in their structure and framework. This article provides an overview of these efforts and discusses the next steps in the implementation of a competency model that is comprehensive enough to be useful, but simple enough to be used. The implications of the competency development process for training, practice, and regulation are discussed.